Problems of assessing students’ knowledge in mathematics using LMS Moodle - Konnova Larisa Petrovna; Lipagina Larisa Vladimirovna; Olekhova Elena Fedorovna; Rylov Alexander Arkadievich; Stepanyan Irina Kimovna (SHS Web of Conferences, 2021)
The widespread introduction of the LMS Moodle educational environment into the educational process in the framework of distance learning and recommendations to use the abovementioned resource for full-time education served as the prerequisites for this study. The authors believe that the knowledge assessment system for distance learning cannot be automatically applied to assess students of other forms of education, but should be adapted to them. The purpose of the research was to study the issues of assessment in the Moodle environment, to develop a methodology for using it to assess the knowledge of students of economic bachelor’s degree in Mathematics. To achieve the goal, scientific literature on this topic was studied, pedagogical design, experiment and student survey were used as research methods. As a result, the authors of the article designed a control and measuring system for assessing knowledge in mathematics in LMS Moodle and the procedure for intermediate certification using this system. The experience of introducing a knowledge assessment system in the first year of the Financial University under the Government of the Russian Federation and a questionnaire survey showed the specificity of approaches to assessing students’ knowledge in an electronic environment in Mathematics. To control the academic achievements of students, the authors consider it necessary to check additionally the performance of the teacher with the subsequent correction of points. The novelty of the research lies in the development of a methodology for using LMS Moodle for assessing students’ knowledge in mathematics in the course of full-time education.